Analyzing youth perceptions as millenial generations oters in an effort to understand democracy, political parties, and the 2024 elections - Sulkiah Hendrawati (Journal of Law Science, 2024)
Currently in Indonesia is in a political nuance where soon the Indonesian people will elect representatives of the people's representatives who will continue the work programs whether continuing with the previous work program or with a new work program where in 2024 the fate of the Indonesian nation will be determined in February on the 14th of 2024 the people's party is a democratic party where. People who already have E-KTP have the right to vote in determining the future of the country here the elections will be held simultaneously in 34 provinces 18 political parties plus 6 local parties from Aceh Province. Millennial youth are currently reluctant to play politics because the level of literacy is not understood by both political parties and elections later in 2024 based on a survey of the term democracy in millennial voters they ignore because of the presence of social media that sees the previous leader there is work after the position is almost over when the new elected butuk wants to be re-elected, so millennial youth are indifferent, rejecting government policies, demonstrations, government / politicians / officials only think of themselves, so millennials currently lack trust, lack of response to the 2024 election.